-3y-1=-2y-8

Simple and best practice solution for -3y-1=-2y-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3y-1=-2y-8 equation:


Simplifying
-3y + -1 = -2y + -8

Reorder the terms:
-1 + -3y = -2y + -8

Reorder the terms:
-1 + -3y = -8 + -2y

Solving
-1 + -3y = -8 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
-1 + -3y + 2y = -8 + -2y + 2y

Combine like terms: -3y + 2y = -1y
-1 + -1y = -8 + -2y + 2y

Combine like terms: -2y + 2y = 0
-1 + -1y = -8 + 0
-1 + -1y = -8

Add '1' to each side of the equation.
-1 + 1 + -1y = -8 + 1

Combine like terms: -1 + 1 = 0
0 + -1y = -8 + 1
-1y = -8 + 1

Combine like terms: -8 + 1 = -7
-1y = -7

Divide each side by '-1'.
y = 7

Simplifying
y = 7

See similar equations:

| 3y-23-6y+31= | | Y+5=-1 | | 2s+3=15 | | -2(7-5m+n)= | | X-(-9)=6 | | x+y+5=60 | | (3x-2)2=13 | | logx+6-logx-4=1 | | 12y-6=139 | | 2(2x-4)=18 | | 7-(4x-5)=2-5x | | 8(3X-4)=4X+8 | | 22=3p-4 | | x-(x+10)=12 | | 6=2y+9 | | (x+3)7= | | 1/z=2/9 | | -3=12+x | | 6y-6=6x-29 | | (i)(8i)(-4+7i)=0 | | 5e(3x-1)=7 | | 4f=30-f | | 2x^2+2=20 | | 2x+5=3y+6 | | 3x-122=88-12x | | 5a-2-3a=2a+4+3a | | 6(7+9x)+2(13-2x)=368 | | 50x+25=70 | | -5/17p=-2 | | 2x+4+2x=180 | | 2x+5=3y-6 | | -8.2-6x-5.8-4x=-9x-8.7 |

Equations solver categories